The Standard of Living in its Relation to Economic Theory and Land Nationalization. Frederic W. Sanders - Davenport, H. J. (Journal of Political Economy, 1899)
preceding it.Probably such is the case.All the errors which have struck the reviewer's eye are in these earlier pages.But a careful revi?sion of the text would serve to remove suspicions which now mar the usefulness of the book.Some of the simpler and more important tables contained in The Universal Cambist have been